Thinking the impossible : French philosophy since 1960 - Gutting, Gary (Oxford University Press, 2013)
Gary Gutting tells the story of the remarkable flourishing of philosophy in France in the last four decades of the 20th century. He examines what it was to 'do philosophy', what this achieved, and how it differs from the Anglophone tradition. His key theme is that French philosophy in this period was mostly concerned with thinking the impossible.